Internet use among university students: A reason for concern? - L. S. (Stephen) Geyer; H. (Herna) Hall; M. P. (Liana) le Roux; G. (Gretel) Crafford (Perspectives in Education, 2018)
International studies reveal that students have more freedom, as well as unstructured and unsupervised time, which makes them susceptible to problematic internet use (PIU). Although students are a risk group for PIU, no evidence of local research on internet use among students could be identified. This article reports on a study on the nature and impact of internet use among students at a tertiary institution. A quantitative research approach was adopted and a survey with a group-administered questionnaire was conducted with 295 second-year students (between 18 and 25 years) registered for a module in a basic social science. Respondents were recruited through convenience sampling. The nature of internet use was explored with reference to internet platforms, reasons for internet use, devices for connecting to the internet, and the locations where respondents access the internet. The impact of internet use was explored through eight constructs adopted from two screening instruments in the public domain, i.e. the Internet-Related Addictive Behaviour Inventory and the Problematic Internet Use Questionnaire. The research results were calculated by means of descriptive and association statistics, specifically the chi-square and Fisher’s exact tests. Ethical considerations, such as informed consent and voluntary participation, were observed. The research results revealed that the respondents preferred email and chatting as internet platforms, while they used the internet mostly for extrinsic reasons, such as for assignments and socialising. Online activities occurred mostly on campus and at home during the early evenings via mobile phones or laptops. The respondents scored relatively low on the constructs measuring PIU. However, two constructs ‘escape from problems’ and ‘loss of control’ presented with markedly higher scores and could be flagged as potential risk areas. Furthermore, association statistics indicated a statistically significant difference of some constructs with regard to gender and the romantic relationship status of respondents, which could be considered in the provision of student support services. The development and evaluation of evidence-based interventions for the prevention, treatment and management of PIU are recommended.